Co-workers' perceptions of the distributive justice of idiosyncratic deals - the roles of content, timing, and justice sensitivity - Pestotnik, Annika (International journal of human resource management, 2024)
Research to date creates a predominantly positive image of idiosyncratic deals (i-deals). However, since i-deals lead to differences in employment relationships, they can trigger perceptions of unfairness and negative reactions among co-workers, thereby posing a threat to the overall effectiveness of i-deals. Against this background, it is important to gain more insights into how co-workers' perceptions of distributive justice are shaped. Building on distributive justice theory and integrating distributive justice principles with the roles of emotions and personality, this study investigates three factors that are likely to influence co-workers' perceptions of the distributive justice of an i-deal: the i-deal's content, the negotiation's timing, and co-workers' justice sensitivity. The results of the vignette-based, between-subjects quasi-experimental study with 650 employees show that these three factors influence co-workers' perceptions of an i-deal's distributive justice. In addition, the results of the study reveal interaction effects between the factors under investigation. By examining what influences co-workers' perceptions of distributive justice, this study contributes to a better understanding of i-deals from a third-party perspective and highlights that some types of i-deals, in terms of content and timing, should be approached with particular caution by supervisors.